Історіографія життєвого шляху та наукового доробку Ю. С. Виноградського - Бойко, Н. (Сiверянський лiтопис, 2015)
У статті схарактеризовано історіографію життєвого шляху та наукового доробку
сосницького краєзнавця Ю. С. Виноградського. Визначено основні періоди дослідницької
праці історика: радянський та сучасний, указані особливості кожного з них. Наголошено на відсутності комплексного дослідження біографії та наукових студій дослідника. В статье схарактеризована историография жизненного пути и научного наследия
сосницкого краеведа Ю. С. Виноградского. Выделены основные периоды исследовательской работы историка: советский и современный, указанные особенности каждого из них. Указано на отсутствие комплексного исследования его биографии и научных исследований. The article characterizes historiography of the lifepath and scientific works of
Yu. Vynohrads’kyi – regional ethnographer from Sosnytsia. The basic periods of historiography:
soviet and modern are distinguished; the main features of each of them are indicated.
The majority of soviet period work sare not very large, written in publicistic style. They in
general highlight biography of Yu. Vynohrads’kyi, the main directions of his scientific work,
the activities connected with foundation of Sosnytsia Regional Ethnography Museum. But
some publications of this period have ideological misrepresentations.
After proclamation of independence of Ukraine the interest to the personality and scientific
works of Yu. Vynohrads’kyi has been increasing. His name is always mentioned with
events connected with Sosnytsia Regional Ethnography Museum that was named after Yu.
Vynohrads’kyi in 1993. Modern s cientists use Yu. Vynohrads’kyi’s works in archeology, local
history, ethnography, dialectology and in their scientific investigations. Nevertheless, his lifepath still has many«white spots». Thus, the absence of complex investigation of biography and scientific studios of the researcher is emphasized.